Densification kinetics of boron carbide with medium entropy alloy as a sintering aid during spark plasma sintering. Issue 1 (23rd July 2018) - Zhang, Mei; Feng, Xiao; Yuan, Tiechui; Li, Ruidi
Abstract: The high sintering temperature of pure B4 C considerably limits its widespread application, thus searching an effective sintering aid is critical. In this work, B4 C‐based ceramic with 1 vol.% nonequiatomic Fe50 Mn30 Co10 Cr10 medium entropy alloy as a sintering aid were fabricated at 1900‐2000°C by spark plasma sintering (SPS) under applied pressure, and their mechanical properties were examined and compared with pure B4 C ceramic sintered at same condition. The maximal flexural strength of 255.59 MPa, microhardness of 2297.6 Hv0.2 and fracture toughness of 3.62 MPa m 1/2 could be obtained at optimized SPS pressure of 50 MPa, which were all higher than those of pure B4 C ceramic. To better understand the densification kinetics mechanisms, the densification ratio as a function of SPS temperature and pressure was theoretically analyzed using steady creep model. It was found that densification controlled by grain‐boundary sliding at lower pressure transferred to power law creep regime at higher pressure, which were proved by the dislocation net shown in transmission electron microscopy image.